(untitled) (Global Journal of Human-Social Science, 2023)
In 1624 the process was opened against Paula de Eguiluz a black slave accused of witchcraft The current text includes all the established legal procedures and the witness statements which reflect the living conditions of the accused and the world around her The document that captures the events at the inquisitorial headquarters has literary resources and transmits detailed information about the realities of its time including personal and collective imaginary in two planes that of the dominant estate and that of the dominated mainly indigenous and African slaves